STUDI LITERATUR PENATALAKSANAAN KEPERAWATAN KEJANG DEMAM PADA ANAK BALITA - Ruslan Hasani; Simunati - Simunati; Sitti - Aminah; Ningsih - Jaya; Rizka - Aulivia (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2023)
A weak immune system in children makes them more susceptible to disease. Especially a fever that develops into a febrile seizure. Febrile seizures can occur due to an increase in body temperature (above 38 ° C checked rectally) this is influenced by processes outside the head or brain without being accompanied by intracranial infection or other causes. The purpose of this study was to determine nursing management, namely body temperature management in the form of warm compresses and tepid sponges in children under five who had febrile seizures. Method : the method used is a study of literature by collecting data from various articles. Results and analysis : based on 10 journal articles that have been reviewed, the results show that body temperature management, especially the provision of warm compresses, can treat febrile seizures in children under five. Discussion and Conclusions: Children under five with febrile seizures are given management in the form of body temperature management, by using warm compresses and tepid sponges to reduce body temperature